Penerapan Metode Cooperative Learning Tipe Student Team Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Siswa - Hamzah, Hamzah; Syarif, Miftah; Herningsih, Herningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research was to find out if the application of cooperative learning method Type Student Team Achievement Division (STAD) can improve student learning outcomes in Islamic Education subjects in grade IV SDN 012 Kualu Mining District Kampar Regency. This research is a Class Action Research (PTK). The subject of this study was a grade 4 student at SDN 012 Kualu. Data collection in this study uses student learning results test. Data analysis techniques use descriptive analysis techniques, which are performed as many as two cycles consisting of six meetings and two Block exams. The result of the research obtained from the absorbency of students in the final test was 76.12% (good category) and the completion of students' learning in the final test was 77.16% which means that classical learning has been completed. In conclusion, the application of cooperative learning method student team achievement division (STAD) can improve the learning outcomes of grade 4 students at SDN 012 Kualu, Kampar Mining District. Keywords: Cooperative Learning, Learning Outcomes, Learning Methods, PAI, STAD